Effect of Auto-exhaust Emissions on Seed Germination of Tree Species Growing along Roadside in Industrial Area of Himachal Pradesh, India - Sharma, Nitika; Singh, Mohinder; Bhardwaj, S. K. (International Journal of Economic Plants, 2018)
Effect of auto-exhaust emissions on the seed germination of tree species growing along roadside was studied at four locations viz., National Highway 21-A (Baddi), Baddi-Barotiwala link road, Kalka-Charnia link road and 200m away from road in Kalka-Charnia Link Road (Control) in BBN industrial area of Himachal Pradesh, India. The seed germination in all the tree species under study decreased in sites where seeds were collected from roadside trees as compared to control where seeds were collected 200m away from road in Kalka-Charnia link road. The germination (%) in Leucaena leucocephala was 4.0, 11.5 and 34.0 in seeds collected from National Highway 21-A (Baddi), Baddi-Barotiwala link road and Kalka-Charnia link road, respectively, against 43.0% seed germination in control. In Toona ciliata, the seed germination was 95.0, 97.0 and 96.5% in National Highway 21-A (Baddi), Baddi-Barotiwala link road and Kalka-Charnia link road, respectively, against 99.0% in control. In Dalbergia sissoo the germination ranged between 94.5 and 97.5% in roadside sites against 99.5% germination in control. The germination energy, germination value and germination speed were also found lower in roadside sites as compared to control in all the species. L. leucocephala has been proved more sensitive to auto-exhaust pollutants as compared to T. ciliata and D. sissoo. Among different sites, National Highway 21- A was found most polluted followed by Baddi-Barotiwala link road and Kalka-Charnia link road.